Estimation of rates of return on social protection: ex ante microsimulation of social transfers in Cambodia. Issue 1 (2nd January 2016) - Mideros, Andrés; Gassmann, Franziska; Mohnen, Pierre
Abstract : This study estimates the rates of return of non-contributory social transfer programmes in Cambodia using household-level data and going beyond standard cost–efficiency analyses by developing a dynamic microsimulation model. It shows that social protection promotes equitable economic growth by enhancing human capital and fostering economic performance at the micro level. A positive rate of return is achieved after 12 periods and can reach between 12 per cent and 15 per cent after 20 periods. This study shows that microsimulation models can be extended in order to analyse the long-term economic returns on social protection.